2021
DOI: 10.22541/au.161651871.11985832/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA barcoding of deep-sea fishes from the northwestern Pacific Ocean: a resource for identifying hidden genetic diversity in deep-sea fishes

Abstract: COI-based DNA barcoding could be an efficient tool for species identification of deep-sea fishes and could lead to the discovery of cryptic species diversity. However, the availability of reference sequences of deep-sea fishes for DNA barcoding is limited, especially for fishes in the northwestern Pacific Ocean. In this study, we performed DNA barcoding of mesopelagic and demersal fish species on the continental shelf and upper slope, collected from deepwater fisheries around Japan and southern Taiwan, to accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Gaither et al [23] noted that sequences of N. microchir in BOLD fall into three BINs, indicating divergent and overlapping lineages. Teramura et al [24] found that N. microchir was divided into four lineages, and two lineages are sympatrically distributed in the northwestern Pacific Ocean and South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Gaither et al [23] noted that sequences of N. microchir in BOLD fall into three BINs, indicating divergent and overlapping lineages. Teramura et al [24] found that N. microchir was divided into four lineages, and two lineages are sympatrically distributed in the northwestern Pacific Ocean and South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…High intraspecific genetic differentiation showed based on COI sequences of samples of Chimaera phantasma (Chimaeridae), Harpadon microchir (Synodontidae), and Pyramodon ventralis (Carapidae). Moreover, for 19 widespread deep-sea fish species, suggested a high level of genetic differentiation for the northwestern Pacific Ocean, that suggest many cryptic species or regional populations not described yet, in deep-sea fishes [40].…”
Section: Cryptic Speciesmentioning
confidence: 98%
“…Nowhere is this more true than in the deep-sea, where new records are continually being made (Bañ on et al, 2020;Mincarone et al, 2022Mincarone et al, , 2014. Not only is a huge amount of the deep sea underexplored, with visual evidence of organisms sparce, but when samples are retrieved from the deep sea they can be prone to taxonomic confusion and have poor diagnostic features (Teramura et al, 2021). Or in the case of soft bodied fish, the difference in pressure can cause them to become disfigured, as the famous blob fish can attest, making morphological identification difficult.…”
mentioning
confidence: 99%